Montevideo Strategy for Implementation of the Regional Gender Agenda within the Sustainable Development Framework by 2030 - NU. CEPAL (ECLAC, 2017)
The Montevideo Strategy for Implementation of the Regional Gender Agenda within the Sustainable Development Framework by 2030 was adopted by the member States of ECLAC at the thirteenth session of the Regional Conference on Women in Latin America and the Caribbean. The aim of the Montevideo Strategy is to guide the implementation of the Regional Gender Agenda and ensure that it serves as a road map for achieving the 2030 Agenda for Sustainable Development at the regional level, from the perspective of gender equality and women’s autonomy and human rights.